Analisis Quality Control Produksi Ikan Tongkol Asap Menggunakan Metode Six Sigma Pendekatan DMAIC - Putra, Anggara Ido Hariyanto; Yusianto, Rindra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Competition among MSMEs is getting tighter, and product quality is key. MSMEs of Smoked Tuna Fish face the problem of defective products that result in losses. This study aims to identify the causes of defects and design risk control strategies. The DMAIC (Define, Measure, Analyze, Improve, Control) method is used as a data-based approach according to the Lean Manufacturing concept. The Six Sigma level is an indicator of production quality, the lower the sigma, the greater the potential for failure, while the higher the sigma, the smaller the possibility of product failure. The results of the study, it is known that the biggest risk in the production process of MSMEs of Smoked Tuna Fish shows the biggest defect is uneven/unripe color (39.60%). For 16 weeks, the average production Sigma level was 4.19. Defects are caused by material, human, machine, and method factors, such as wet coconut shells, high water content, lack of skills, SOPs, and limited tools. Proposed improvements include the use of dry coconut shells, drying fish, worker training, improving tools with optimal smoke circulation, and standardizing SOPs to maintain quality consistency.